Avaliação comparativa do número de mastócitos na muscular circular do esôfago e do colón de chagásicos crônicos com e sem mega. - PINHEIRO, Simone Wanderley (2006)
With the objective of comparatively evaluate the number of mast cells in the circular musculature of the esophagus and the normal colon, and to verify if there is an increase of the number of mast cells in the esophagus and colon of chronic chagasics with and without mega, we counted the number of mast cells and evaluated semi-qualitatively myositis and fibrosis aiming to contribute to the pathogenesis of the lesions of mega cchagasic ones. 28 cases of necropsy were studied, being 12 non-chagasic controls, 10 chagasic without megas and 6 chagasic with megacolon and megaesophagus. A ring in the rectal sigmoid transition was drawn and another one in the lower third of the esophagus, 5 cm of the cardia of all the cases. The rings were fixed in formol 4% and processed for an inclusion in paraffin. Histological cuts were stained by the hematoxylin-eosin, Giemsa and Tricrômico of Masson techniques. Mast cells were counted in microscopic fields of common light, LEICADIASTAR model (total area: 12. 6mm², in cuts stained by Giemsa technique. Myositis was semi-quantitatively evaluated and the fibrous connective tissue in cuts stained by hematoxylin-eosin and Tricrômico of Masson techniques. These alterations were classified in discrete, moderate or intense ones. The following conclusions synthesize our analysis: 1. In the musculature of the esophagus there was no statistically significant difference between the number of mast cells in the chagasic subjects with megaesophagus, related to the chagasic ones without mega and to the non-chagasic ones. 2. In the musculature of the colon there was no statistically significant difference between the number of the mast cells in the chagasic subjects with megacolon, related to the chagasic ones without mega and to the non-chagasic ones. 3. The number of mast cells in the esophagus was much higher than in the colon in all of the groups, what indicates a structural difference between these two organs. 4. There was not a statistically significant difference between the frequency of myositis in the chagasic group with mega related to the chagasic ones without mega. 5. Substitution fibrosis and interstitial fibrosis were seen more frequently in the chagasic group with mega, related to the chagasic ones without mega.